Pengaruh Suplementasi Vitamin D Pada Kesehatan Tulang - Ramadhani, Fitri; Siba, Salma salsabila; Yulia, Asri (Prodi Farmasi Fakultas Kedokteran Universitas Hang Tuah, 2024)
Vitamin D is a key nutrient that plays an essential role in maintaining bone integrity through the regulation of calcium and phosphorus metabolism. Prolonged vitamin D deficiency leads to reduced bone mineral density and an increased risk of osteoporosis and fractures, particularly among older adults. This article presents a literature review of three scientific journals that examine the relationship between vitamin D supplementation, bone mineral density, and fracture prevention. The synthesized literature indicates that a supplementation dose of 800–1000 IU/day—especially when combined with calcium—provides significant protective effects on bone health. Higher doses do not offer additional meaningful benefits and may increase the risk of hypercalcemia. Thus, vitamin D serves as a strategic preventive intervention that can be considered for maintaining long-term bone health